Herbal medicine used in the treatment of cardiovascular diseases in the Rif, North of Morocco - Chaachouay, Noureddine; Azeroual, Abdelhamid; Bencharki, Bouchaib; Zidane, Lahcen (Frontiers in Pharmacology, 2022)
Background: Since the dawn of time, Moroccans have used medicinal plants as a popular remedy to treat a wide range of human and cattle health issues. Nonetheless, very little research has been conducted in the past to record and disseminate indigenous ethnopharmacological knowledge adequately.This study was conducted in the Rif and attempted to identify medicinal plants used by indigenous people to treat cardiovascular problems and the ethnomedicinal knowledge linked with them. Methods: The ethnobotanical study was carried out in the Moroccan Rif area over two years, from 2016 to 2018. We questioned 520 traditional herbalists and consumers of these herbs in total. The gathered data were examined and contrasted using quantitative ethnobotanical indicators such as family importance value (FIV), the relative frequency of citation (RFC), plant part value (PPV), fidelity level (FL), and informant consensus factor (ICF). Results: The findings analysis revealed the presence of 33 plant species classified into 20 families, with the Poaceae dominating (7 species). Regarding disorders treated, the category of cardiac arrhythmias has the greatest ICF (0.98). The study discovered that the leaves were the most often utilized portion of the plants (PPV=0.353) and that the most frequently used preparation was a decoction (31%). Conclusions: The current study's findings revealed the presence of indigenous ethnomedicinal knowledge of medicinal plants in the Moroccan Rif to treat cardiovascular illnesses. Further phytochemical, pharmacological, and toxicological investigations should be conducted to identify novel drugs from these documented medicinal plants.